Evaluating the availability of electronic banking service quality requirements in public banks " A field study on public banks in the city of "Damascus - سكيف نسرين; سامر قاسم; رامي محمد (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This study aimed to evaluate the availability of quality requirements for the electronic banking service provided in public banks in the city of Damascus, by studying each of the dimensions (administrative requirements, human requirements, technical requirements, financial requirements, and security and peace requirements). The researcher relied on the descriptive approach as a general approach to research, and relied on the statistical analysis method to test the hypotheses, where she collected data through a questionnaire that was distributed to 85 items as a facilitated sample of workers in the middle and upper administrative levels in public banks, and a set of statistical methods were used. Among them is the single-sample Student test. The researcher reached a set of results, including Human requirements, technical requirements, and safety and security requirements are all met for the quality of electronic banking services provided in public banks in the city of Damascus. Both the administrative and financial requirements for the quality of electronic banking services are not met in public banks in the city of Damascus.